The Responsibility to Protect in Darfur : the Role of Mass Media. - Sidahmed, Abdel Salam (Lexington Books, 2010)
The Responsibility to Protect in Darfur traces the development of international intervention in domestic conflict, culminating in the concept of ''Responsibility to Protect'' in 2001. The authors explain the background and complexity of the crisis besetting Darfur, and document U.S. media coverage of the crisis in terms of framing that would mobilize public opinion behind international intervention.